Iron and Zinc Foliar Spraying Affected Sideritis cypria Post. Growth, Mineral Content and Antioxidant Properties - Chrysargyris, Antonios; Tzortzakis, Nikos G. (My University, 2025)
Species of the genus Sideritis are gaining heightened recognition for their applications in both culinary and industrial contexts. The improvement of crop cultivation techniques to promote the quality of the final product is imperative nowadays for ensuring sustainable and successive agricultural production, especially for medicinal and aromatic plant species. The present study examined the impacts of foliar application of iron (Fe) and zinc (Zn) on Sideritis cypria plants grown in hydroponics. The spraying of Fe (1.79 mM and 10.79 mM) and Zn (1.74 mM and 10.43 mM Zn) was applied four times at 10-day intervals, and the effects on plant growth, plant physiology, antioxidant status and nutrient uptake were investigated. The applications of both the high Fe and Zn levels decreased the plant yield and dry matter content. The use of the high Fe levels, particularly, resulted in elevated oxidative stress, as indicated by the increased levels of lipid peroxidation and hydrogen peroxide production and the increased peroxidase enzymatic activity. The application of the high Fe levels (10.79 mM Fe) also induced the plants' non-enzymatic antioxidant mechanisms and the total flavonoid content. All foliar applications increased the accumulation of sodium in the leaf tissue. The plants' calcium content was increased after the treatment with Zn, while the magnesium content was increased only when the high Zn level (10.43 mM Zn) was applied. Interestingly, the foliar application of both Zn and Fe had no effect on the build-up of zinc or iron content in the leaf tissue. Biofortification with minerals is a key approach to enhancing the biological quality and the nutritional value of plants, while its foliar application or application via different fertigation strategies needs to be evaluated either as single or as combined practices.
Keywords: Sideritis spp.; antioxidants; biofortification; hydroponics; microelements